Trastorno bipolar en el embarazo - Segura Villalobos, Yendry (2019)
Bipolar disorder is a chronic disorder characterized by unusual intense mood shifts ranging from mania to depression. It affects an important percentage of the world population, and to women in their reproductive years. In pregnancy, it has deleterious effects on the fetus development, and it represents a big risk for the mother: self-injury, drugs abuse and suicide. Diagnosis is the most challenging step in management, because it determines the treatment plan, which is completly different than other psiquiatric disorder plan.  Common drug classes used in pregnancy are lithium, atypical antipsychotics and lamotrigine. The purpose of this article is to inform about this mental illness, the risks of non-medication and the challenges involved in the treatment.